Perioperative adrenal crisis unmasking previously undiagnosed secondary adrenal insufficiency in a young woman with acute appendicitis: a case report - Kevadiya, Ruchik; Ghantiwala, Kunj R.; Dey, Proma; Nguyen, Darlene; Saleh, Ahmed (International Journal of Research in Medical Sciences, 2026)
Secondary adrenal insufficiency often presents with vague, nonspecific symptoms and may remain undiagnosed until physiological stress precipitates adrenal crisis. A 19-year-old female presented with right lower quadrant abdominal pain, nausea, and light-headedness. Imaging findings were suspicious for acute appendicitis, and laparoscopic appendectomy was performed. Further history revealed a three-year history of intermittent dizziness, headaches, poor appetite, and generalized weakness that had never been evaluated. On admission, she had marked bilateral lower limb weakness despite unremarkable magnetic resonance imaging of the brain and spine. Laboratory evaluation demonstrated a morning cortisol level of 1.12 μg/dl, and subsequent testing revealed suppressed adrenocorticotropic hormone levels, consistent with secondary adrenal insufficiency. Following surgery, the patient developed hypotension, tachycardia, and tachypnoea despite initial management, raising concern for perioperative adrenal crisis. She responded to intravenous fluids and stress-dose hydrocortisone with rapid haemodynamic stabilization and gradual improvement in symptoms and mobility. This case highlights the diagnostic challenge of secondary adrenal insufficiency in young patients with longstanding nonspecific symptoms, particularly in the absence of characteristic electrolyte abnormalities. It also emphasizes that acute illness and surgical stress may unmask previously unrecognized adrenal insufficiency and underscores the importance of prompt recognition and glucocorticoid therapy to prevent potentially life-threatening complications.